Ecosystem transpiration and evaporation: Insights from three water flux partitioning methods across FLUXNET sites. (6th October 2020) - Nelson, Jacob A.; Pérez‐Priego, Oscar; Zhou, Sha; Poyatos, Rafael; Zhang, Yao; Blanken, Peter D.; Gimeno, Teresa E.; Wohlfahrt, Georg; Desai, Ankur R.; Gioli, Beniamino; Limousin, Jean‐Marc; Bonal, Damien; et al.
Abstract: We apply and compare three widely applicable methods for estimating ecosystem transpiration ( T ) from eddy covariance (EC) data across 251 FLUXNET sites globally. All three methods are based on the coupled water and carbon relationship, but they differ in assumptions and parameterizations. Intercomparison of the three daily T estimates shows high correlation among methods ( R between .89 and .94), but a spread in magnitudes of T /ET (evapotranspiration) from 45% to 77%. When compared at six sites with concurrent EC and sap flow measurements, all three EC‐based T estimates show higher correlation to sap flow‐based T than EC‐based ET. The partitioning methods show expected tendencies of T /ET increasing with dryness (vapor pressure deficit and days since rain) and with leaf area index (LAI). Analysis of 140 sites with high‐quality estimates for at least two continuous years shows that T /ET variability was 1.6 times higher across sites than across years. Spatial variability of T /ET was primarily driven by vegetation and soil characteristics (e.g., crop or grass designation, minimum annual LAI, soil coarse fragment volume) rather than climatic variables such as mean/standard deviation of temperature or precipitation. Overall, T and T /ET patterns are plausible and qualitatively consistent among the different water flux partitioning methods implying a significant advance made for estimating and understanding T globally, while the magnitudes remain uncertain. Our results represent the first extensive EC data‐based estimates of ecosystem T permitting a data‐driven perspective on the role of plants' water use for global water and carbon cycling in a changing climate. Abstract : While transpiration ( T ) from plants has been studied for centuries, it is difficult to measure at ecosystem scale. We explore three new methods for estimating T from existing eddy covariance data from FLUXNET, providing insights into how plants use water at over 251 sites across the globe. Though there is still work to be done to constrain the magnitude of T, we show that this new dataset represents a significant step toward bridging the gap between individual plant measurements and global estimates of plant water use. Photo credit to Tiana Wilene Hammer.